Synthesis of Carboxamides and Carbothioamides of Phthalimide: Molecular Modeling and Biological Investigation - Gavadia, Renu; Rasgania, Jyoti; Jakhar, Komal (Asian Journal of Chemistry, 2022)
A series of carboxamide and carbothioamide derivatives of phthalimide have been synthesized efficiently by employing water as a green reaction media. The synthesized N-substituted phthalimide derivatives have been characterized by spectroscopic, elemental and their quantum parameters, including molecular orbital energies are deduced by DFT modeling. The molecular docking of synthesized derivatives against B-DNA (pdb:1bna) displays favourable binding interactions and satisfactory docking scores, predicting their significant antimicrobial efficacy. The synthesized phthalimide derivatives were screened for in vitro antimicrobial and antioxidant activity using broth microdilution method and DPPH radical scavenging assay, respectively. Some of the title compounds exhibited promising the antimicrobial and antioxidant potential. The pharmacokinetics parameters and bioavailability of the title compounds were accessed by in silico ADMET analysis to envisage their drug efficacy.